KANDUNGAN ZAT GIZI, VITAMIN, DAN MINERAL SNACK BAR PREBIOTIK BERBASIS EDAMAME DAN TANAMAN HERBAL LOKAL - Putri Rahayu Ratri; Miftahul Jannah; Sabran Sabran; Surya Dewi Puspita (Jurnal Agriovet, 2023)
The local food-based snack bar has the potential to be developed to support stunting prevention programs in toddlers. Edamame and herbal plants (such as ginger rhizome, cinnamon, and lempeni leaf powder) can be used in the development of snack bars as a functional food. This research is experimental research with a laboratory analysis method. The snack bar formulation has previously been calculated using the Nutrisurvey for Linear Programming application. Two formulations and one control were obtained and then tested for their nutritional content. Research parameters were tested by proximate test (carbohydrate content, total fat, protein, total energy, energy from fat, water content, ash content, and dietary fiber, as well as the mineral content of iron (Fe), Zinc (Zn), and Vitamin C. The results showed that most of the mineral content, vitamins, dietary fiber, ash content, water content, and protein content of Formula 1 and 2 had better content than the control. However, the energy, carbohydrate, and fatcontent of Formula 1 and 2 show a lower amount than the control. The addition of several ingredients such as edamame, lempeni leaves, and some herbs such as ginger and cinnamon can improve the nutritional quality of snack bar.